2022
DOI: 10.1038/s41597-022-01490-4
|View full text |Cite
|
Sign up to set email alerts
|

A high-resolution climate simulation dataset for the past 540 million years

Abstract: The Phanerozoic Eon has witnessed considerable changes in the climate system as well as abundant animals and plant life. Therefore, the evolution of the climate system in this Eon is worthy of extensive research. Only by studying climate changes in the past can we understand the driving mechanisms for climate changes in the future and make reliable climate projections. Apart from observational paleoclimate proxy datasets, climate simulations provide an alternative approach to investigate past climate condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 41 publications
0
35
1
Order By: Relevance
“…As is pointed out in Li et al. (2022) and in the Methods section, the overestimated CO 2 concentrations in the Control group of simulations are mainly related to two major factors. One is the ECS of the model.…”
Section: Conclusion and Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…As is pointed out in Li et al. (2022) and in the Methods section, the overestimated CO 2 concentrations in the Control group of simulations are mainly related to two major factors. One is the ECS of the model.…”
Section: Conclusion and Discussionmentioning
confidence: 66%
“…Detailed description of the model used here, model setup, and simulation initialization has been documented in the preceding paper by Li et al. (2022). It is worth noting that the results presented in this study are from the fully coupled model (see below), while the results in Li et al.…”
Section: Methodsmentioning
confidence: 99%
“…In the first set, both solar insolation and CO 2 concentrations are prescribed as shown in Table 1 of Li et al. (2022). Solar insolation increases linearly with time from 1333.78 to 1360.89 W m −2 following Gough (1981).…”
Section: Data and Experimentsmentioning
confidence: 99%
“…Moreover, Xia, Huang, & Hu (2020) found that the increase in SWV is accelerated under greenhouse warming. It is important to note that the global mean surface temperature (GMST) variations over the past 250 Myr, which is as large as about 12 K, are much stronger than present‐day and future global warming based on climate models (Li et al., 2022; Scotese et al., 2021). These results raise important questions: how does SWV change associated with the large temperature variations over tectonic timescales?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation